(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
Humans have the power to act as both experimental creators and careful observers within the sets of living creations and systems which move in ways both inside and outside of our control. In this unique position, we have the choice (personally and as a part of the collective sum of our parts) to move toward peace with intention, by taking the principles of elements inside our control into actionable consideration. This intention also requires an understanding of the elements of peace, its processes, and evidence for and against its existence across sets of realities. Peace is a fundamental component of basic human rights, and evidence of peace is evidence of justice. Snauwaert (2022) identifies peace’s fundamental connection to social organization and describes peace as both the operative absence of structural violence and the functional presence of structural justice, consisting of variations in value, relating to its substantial nature, and spheres, relating to the spaces it occupies. Peace encompasses the foundational elements of security and justice which all humans in any society, under any nation or agency, are owed (Snauwaert, under review).